Genetic Modification for Improving Seed Vigor Is Transitioning from Model Plants to Crop Plants - Wu, Xiaolin; Ning, Fen; Hu, Xiuli; Wang, Wei (Frontiers in Plant Science, 2017)
Although seed vigor is a complex physiological trait controlled by quantitative trait loci, technological advances in the laboratory are being translated into applications for enhancing seed vigor in crop plants. In this article, we summarize and discuss pioneering work in the genetic modification (GM) of seed vigor, especially through the over-expression of protein L-isoaspartyl methyltransferase (PIMT, EC 2.1.1.77) in seeds. The impressive success in improving rice seed vigor through the over-expression of PIMT provides a valuable reference for engineering high-vigor seeds for crop production. In recent decades, numerous genes/proteins associated with seed vigor have been identified. It is hoped that such potential candidates may be used in the development of genetically edited crops for a high and stable yield potential in crop production. This possibility is very valuable in the context of a changing climate and increasing world population.